Enhancing food waste compost quality with nutrient amendments - John Nkansah; Samson Oduro-Kwarteng; Helen Essandoh; Richard Kuffuor (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Recycling of food waste fraction of municipal solid waste into compost for use in agriculture is seen as an effective environmentally–friendly option. In developing countries, however, there are few commercial composting facilities producing composts whose use in agriculture is low, mainly due to their low nutrient content compared to chemical fertilizers.Method This study investigated the effect of the food waste (FW) nutrient-amendment ratio on compost quality using amendments such as Cocoa Pod Husk Ash (CPHA), poultry manure (PM), and cow manure (CM). Six treatments (T1, T2, T3, T4, T5, and T6) and control were composted for 70 days.Results The total Nitrogen, total Phosphorous, and total Potassium content ranged from 0.96–1.42%, 0.19–0.78%, and 0.86-1.42%, respectively, for the different compost types. In all treatments, the C/N ratio reduced significantly, while concentrations of heavy metals (Pb and Zn) were within the acceptable international limits. Toxicity of composts to cucumber (Cucumis sativus) was ascertained. Germination index (GI) was the highest in T5 (FW amended with PM only) whereas the control (FW only) recorded the least GI. Conclusion This study shows that the use of PM, CM, and CPHA seems to be beneficial for the enrichment of food waste compost.